(untitled) (Bangladesh Journal of Pharmacology, 2012)
Endophytic microorganisms are fungi or bacteria that live inside the healthy tissues of the host plants causing no apparent symptoms of diseases. Five endophytic fungal strains labeled as IR-1, IR-2, IR-4, IR-6 and IR-7 (identified as Penicillium thiomii) were isolated from the medicinal plant of Terminalia chebula Retz by culture and sub-culture. The ethyl acetate extract of fungal strains, IR-4, IR-6 and IR-7 inhibited the growth of CaCo-2 colon cancer cell lines in MTT assay with IC50 values of 55, 44 and 67 µg/mL, respectively.